Estimates of RF-induced erosion at antenna-connected beryllium plasma-facing components in JET. (18th January 2016) - Klepper, C C; Borodin, D; Groth, M; Lasa, A; Airila, M; Bobkov, V; Colas, L; Jacquet, P; Kirschner, A; Terra, A; Biewer, T M; Delabie, E; et al.
Abstract: Radio-frequency (RF)-enhanced surface erosion of beryllium (Be) plasma-facing components is explored, for the first time, using the ERO code. The code is applied to measured, RF-enhanced edge Be line emission at JET Be outboard limiters, in the presence of high-power, ion cyclotron-resonance heating (ICRH) in L-mode discharges. In this first modelling study, the RF sheath effect from an ICRH antenna on a magnetically connected, limiter region is simulated by adding a constant potential to the local sheath, in an attempt to match measured increases in local BeI and BeII emission of factors of 2–3. It was found that such increases are readily simulated with added potentials in the range of 100–200 V, which is compatible with expected values for potentials arising from rectification of sheath voltage oscillations from ICRH antennas in the scrape-off layer plasma. Absolute erosion values are also estimated within the uncertainties in local plasma conditions.